2000
DOI: 10.1002/1521-3765(20000703)6:13<2338::aid-chem2338>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Structural Properties of a Homologous Series of Bis-diphenylphosphine Oxides

Abstract: A homologous series of bis-diphenylphosphine oxides (C6H5)2PO(CH2)(n)PO(C6H5)2 (with n = 2-8; denoted 2-8] have been investigated to explore the effects of a range of competing and cooperative intermolecular and intramolecular interactions on the structural properties in the solid state. The important factors influencing the structural properties include intramolecular aspects such as the conformation of the aliphatic chain and the intramolecular interaction between the two P=O dipoles in the molecule, and int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
1
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 13 publications
4
53
1
1
Order By: Relevance
“…The OseOs bond lengths in 1 and 2 fall in the range from 2.847(2) to 2.9255(2) Å and the Os(1)eP(1) bond lengths are equal to 2.352(5) and 2.361(6) Å, respectively. As a result, the observed values of the bond lengths are comparable to those in other previously reported [Os 3 (CO) 11 (2) Å in 2, are similar to those found in free phosphane oxides [27,28]. In addition, 1 and 2 comprise coordination sites at the O(12) atom of the DPMO that are accessible for further electrophilic attack of a Lewis acid.…”
Section: Resultssupporting
confidence: 89%
“…The OseOs bond lengths in 1 and 2 fall in the range from 2.847(2) to 2.9255(2) Å and the Os(1)eP(1) bond lengths are equal to 2.352(5) and 2.361(6) Å, respectively. As a result, the observed values of the bond lengths are comparable to those in other previously reported [Os 3 (CO) 11 (2) Å in 2, are similar to those found in free phosphane oxides [27,28]. In addition, 1 and 2 comprise coordination sites at the O(12) atom of the DPMO that are accessible for further electrophilic attack of a Lewis acid.…”
Section: Resultssupporting
confidence: 89%
“…The structure determination of Ph 2 P(O)(CH 2 ) 7 P(O)Ph 2 ,57 which is described in detail in Section 3.3, was also part of a wider crystal‐engineering study58 of materials in the family Ph 2 P(O)(CH 2 ) n P(O)Ph 2 . The structure solution of the unsolvated crystal form of Ph 2 P(O)(CH 2 ) 5 P(O)Ph 2 has also been tackled recently from powder diffraction data 59…”
Section: Examples Of Structure Determination From Powder Diffractimentioning
confidence: 99%
“…This has been observed in phosphine oxides, which can form extended structures through strong P-O and H-C interactions. [24] Burrows et al [22] observed a similar phenomenon and attributed these shifts to aggregation rather than the formation of excimers, as no change was observed in either the UV-visible absorption or the excitation scan for corresponding emissions.…”
Section: Photophysical Propertiesmentioning
confidence: 83%